TETRA‐EU 1.0: A species‐level trophic metaweb of European tetrapods. Issue 9 (14th June 2020) - Maiorano, Luigi; Montemaggiori, Alessandro; Ficetola, Gentile Francesco; O'Connor, Louise; Thuiller, Wilfried
Abstract: Motivation: Documenting potential interactions between species represents a major step towards understanding and predicting the spatial and temporal structure of multi‐trophic communities and their functioning. The metaweb concept summarizes the potential trophic (and non‐trophic) interactions in a given species pool. As such, it generalizes the regional species pool of community ecology by incorporating the potential relationships between species from different trophic levels along with their functional characteristics. However, although this concept is very attractive theoretically, it has rarely been used to understand the structure of an ecological network, mostly because of data availability. Here, we provide a continental‐scale, species‐level metaweb for all tetrapods (mammals, breeding birds, reptiles and amphibians) occurring in Europe and in the Northern Mediterranean basin. This metaweb is based on data extracted from the scientific literature, including published papers, books and grey literature. Main type of variable contained: For each species considered, we built the network of potential two‐way trophic interactions. Spatial location and grain: We considered all species occurring in the entire European subcontinent, from Macaronesia (including only the islands belonging politically to Spain and Portugal) to the Ural Mountains (west to east) and from Fennoscandia and U.K. islands to the Mediterranean (north to south). We included Turkey, geographically part of Asia, to provide a complete picture of the north‐eastern Mediterranean coast. Time period: The data represent information published and/or collected during the last 50 years. Major taxa studied and level of measurement: We focused our metaweb on terrestrial tetrapods occurring in the study area. Only species introduced in historical times and currently naturalized were considered; new introductions were excluded. In total, we included 288 mammals, 509 regularly breeding birds, 250 reptiles and 104 amphibians. Software format: Data are supplied as semicolon‐separated text files.